HUBUNGAN USIA, PARTUS LAMA DAN GAWAT JANIN PADA IBU HAMIL DENGAN SECTIO CAESAREA DI RSUD H. ABDUL MANAP KOTA JAMBI - Olivia Tri Monica; Mawaddah Tul Khamisya; Reni Hariyanti; Silvia Mariana (Poltekkes Kemenkes Jambi, 2023)
Background: Sectio Caesarea (SC) continues to increase worldwide, especially in middle and high-income countries, and has become a major and controversial public health problem (Torloni, et al, 2014). According to data from the World Health Organization (WHO) the average Sectio Caesarea procedure ranges from 5% to 15% per 1000 world births. Method: this research is quantitative, with a retrospective approach. The population in this study were all mothers giving birth at H. Abdul Manap Hospital, Jambi City, totaling 70 people. The sampling technique uses Simple Random Sampling. Data analysis used univariate and bivariate analysis with statistical tests using chi square. Includes population, sample, method of research written concisely and clearly Result: The results of the research that has been carried out are obtained from the results of data analysis using the Chi Square statistical test showing that the factors associated with sectio caesarea deliveries are prolonged labor p-value = 0.042 (≤ 0.05), fetal distress p-value = 0.002 (≤ 0.05) , while the age that is not related is p-value = 0.903% (> 0.05). Conclusion : It can be concluded that there is a relationship between prolonged labor and fetal care with Sectio Caesarea and there is no relationship between maternal age and Sectio Caesarea at H. Abdul Manap Hospital, Jambi City.